2019
DOI: 10.1136/bmjopen-2019-031890
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of antenatal care utilisation in sub-Saharan Africa: a systematic review

Abstract: ObjectivesTo identify the determinants of antenatal care (ANC) utilisation in sub-Saharan Africa.DesignSystematic review.Data sourcesDatabases searched were PubMed, OVID, EMBASE, CINAHL and Web of Science.Eligibility criteriaPrimary studies reporting on determinants of ANC utilisation following multivariate analysis, conducted in sub-Saharan Africa and published in English language between 2008 and 2018.Data extraction and synthesisA data extraction form was used to extract the following information: name of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

71
288
7
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(369 citation statements)
references
References 115 publications
(304 reference statements)
71
288
7
3
Order By: Relevance
“…As modeling is the common approach in assessing the relationship between health variables and their determinants, modeling URAC for the two years of 1995 and 2014 was carried out. The modeling of URAC con rmed the ndings in previous literature on developing countries, and on Egypt [11][12][13][14][15][16][17][18][19][20][21]: both social and health needs were signi cant in determining URAC. On the social side, women's age at birth, their education level, their husbands' education level, the household standard of living/wealth, and the region, were signi cant determinants of URAC.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…As modeling is the common approach in assessing the relationship between health variables and their determinants, modeling URAC for the two years of 1995 and 2014 was carried out. The modeling of URAC con rmed the ndings in previous literature on developing countries, and on Egypt [11][12][13][14][15][16][17][18][19][20][21]: both social and health needs were signi cant in determining URAC. On the social side, women's age at birth, their education level, their husbands' education level, the household standard of living/wealth, and the region, were signi cant determinants of URAC.…”
Section: Discussionsupporting
confidence: 76%
“…Some research efforts have focused on understanding the main determinants of any use or of regular use of antenatal care. As in the literature on determinants of antenatal care use in developing countries [11][12][13][14][15][16], research in Egypt has con rmed the importance of both social and health needs as determinants of antenatal care. On the social side, women's age or age at birth, their education, their husbands' education level, the women's work status, the household standard of living/wealth, and place of residence, assessed in terms of regional level or by rural/urban differentiation, were identi ed as signi cant determinants of antenatal care [17][18][19][20].…”
Section: Determinants and Inequality Of Antenatal Care In Egyptmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, socioeconomic status of the woman was also a challenge. Several studies showed that good economic status of the woman enables her to complete the required number of BP check-ups [19,22,23]. Moreover, a systematic review study that included 74 studies found out that low parity was associated with adequate ANC service utilization [23].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies showed that good economic status of the woman enables her to complete the required number of BP check-ups [19,22,23]. Moreover, a systematic review study that included 74 studies found out that low parity was associated with adequate ANC service utilization [23]. Women with high parity tend to under-utilize ANC services, thus missing the opportunity to have their blood pressure adequately checked [24,25].…”
Section: Introductionmentioning
confidence: 99%